Digital Transformation in Quran Village Education: A “Smart Tahfidz” App for Sustainability Learning - Irany Windhyastiti; Umu Khouroh; Sri Wahyu Lelly Hana Setyanti; Syarif Hidayatullah; Shafa Sabrina Nafarinka (Proceedings of International Conference of Graduate School on Sustainability, 2026)
Kampoeng Qur’an is one of the religious education tourism sites in Malang City that offers many types of Qur’an learning. Qur’an learning is conducted in 3 large mosques, 15 Qur’an Houses, and 13 TPQs, totaling 70 classes. There is one “Tahfidz Class” (Quran memorization class) held on weekends. Because many of the students are from out of town, it would be easier to utilize information technology to facilitate access to materials and reporting of learning outcomes. Therefore, a “Smart Tahfidz” application was created to make it easier for students to access materials and view learning outcome reports. The development of a “Smart Tahfidz” Digital Application Model uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) Method in Android Studio. The digital transformation enabled by the “Smart Tahfidz” app has positively impacted the education system in Quran Villages. The application enhances the efficiency of the Quran memorization process while strengthening evaluation, monitoring, and reporting mechanisms that were previously managed manually. The existence of “Smart Tahfidz” is also expected to encourage the sustainability of education in Kampoeng Qur’an.